Pengaruh Lingkungan Kerja Dan Semangat Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Abs Raya Rubber Works - Febrilian Lestario (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine whether a work environment and working spirit together influence the performance of employee at PT ABS Raya Rubber Works. Data collection techniques in this study was a questionnaire (Questionnaire), study of documents and interviews (Inteview). While the data analysis techniques used are validity, reliability test, the classical assumption test, multiple linear regression, F test and t test. Results of this study demonstrate that the variable working environment and working spirit partially significant effect on labor productivity at PT ABS Raya Rubber Works. Based on the results of the F test can be proved that the work environment and working spirit positive and significant impact on performance of employees at PT ABS Raya Rubber Works.